Long-term exposure to PM2.5 and incidence of acute myocardial infarction - Madrigano, Jaime; Kloog, Itai; Goldberg, Robert; Coull, Brent A; Mittleman, Murray A; Schwartz, Joel (Environmental health perspectives, 2013)
A number of studies have shown associations between chronic exposure to particulate air pollution and increased mortality, particularly from cardiovascular disease, but fewer studies have examined the association between long-term exposure to fine particulate air pollution and specific cardiovascular events, such as acute myocardial infarction (AMI). We examined how long-term exposure to area particulate matter affects the onset of AMI, and we distinguished between area and local pollutants. Building on the Worcester Heart Attack Study, an ongoing community-wide investigation examining changes over time in myocardial infarction incidence in greater Worcester, Massachusetts, we conducted a case-control study of 4,467 confirmed cases of AMI diagnosed between 1995 and 2003 and 9,072 matched controls selected from Massachusetts resident lists. We used a prediction model based on satellite aerosol optical depth (AOD) measurements to generate both exposure to particulate matter ≤ 2.5 μm in diameter (PM2.5) at the area level (10 × 10 km) and the local level (100 m) based on local land use variables. We then examined the association between area and local particulate pollution and occurrence of AMI. An interquartile range (IQR) increase in area PM2.5 (0.59 μg/m3) was associated with a 16% increase in the odds of AMI (95% CI: 1.04, 1.29). An IQR increase in total PM2.5 (area + local, 1.05 μg/m3) was weakly associated with a 4% increase in the odds of AMI (95% CI: 0.96, 1.11). Residential exposure to PM2.5 may best be represented by a combination of area and local PM2.5, and it is important to consider spatial gradients within a single metropolitan area when examining the relationship between particulate matter exposure and cardiovascular events.